Ruddlesden–Popper 2D Chiral Perovskite‐Based Solar Cells. Issue 8 (5th June 2022) - Shpatz Dayan, Adva; Wierzbowska, Małgorzata; Etgar, Lioz
Abstract : In this work, 2D chiral perovskite is demonstrated, where the barrier molecules are the two enantiomers (R)‐(+)‐α‐Methylbenzylamine (R‐MBA) and (S)‐(‐)‐α‐Methylbenzylamine (S‐MBA). The chirality is manifested at high χ values and pure 2D structure measured by circular dichroism (CD) (where the perovskite general formula is ABX3 χ (S/R‐MBA)2 PbI4, χ is the ratio of the barrier molecule to the small cation (A + )). The anisotropy factor ( g abs ) decreased by an order of magnitude when decreasing the χ value achieving 0.0062 for pure 2D. Ab initio many‐body perturbation theory successfully describes the bandgaps, absorbance, and CD measurements. For the first time, these quasi‐2D chiral perovskites are integrated into the solar cell. Using circular polarization (CP) and cutoff filter, the chirality effect from the solar cells photovoltaic response is able to be distinguished. It is revealed that at high χ values, the chirality affects the current density of the solar cell more than at low χ values while the open‐circuit voltage didn't change. These chiral 2D perovskite are new class of materials which open the way for polarized hybrid perovskite. Abstract : In this work, 2D chiral perovskite is demonstrated. The chirality is manifested at pure 2D perovskite with anisotropy factor ( g abs ), which is decreased by an order of magnitude when decreasing the dimensionality achieving a value of 0.0062 for pure 2D. It is revealed that at low dimensionality the chirality affects the current density of the solar cell.